Hotel marketing strategies - Eng, Keng Boon (2008)
This study attempts to examine the marketing strategies adopted by local hotel establishments in the competitive hospitality industry. It also analyzes the role of information technology in strategic marketing and delves on the repercussions of the Asian Economic Crisis on hotels. Finally, it strives to compare and contrast the survey results obtained from local hotels with that of U.S. hotels in hope of discovering valuable insights.